Architecture of the Machine - Gild, Talia Orli (School of Architecture, Planning and Geomatics, 2018)
A dissertation born out of the fascination of largescaled infrastructural engineered/architectural projects, where the individual human is absent from its initial architectural and programmatic goals, rendering built form/architecture that is free to explore scale and form. A project where the architecture is formally governed by a process that is mechanical and systematic. This dissertation that has been entitled Architecture of the Machine as I have chosen to explore the machine of our future water supply, that of a desalination plant. 2013 marks the year that we, South Africa, are no longer water "secure", in other words, the population of the country is going to exceed the amount of water available to us. A desalination plant in Hout Bay, able to produce 30 000M ℓ/day, situated on the edge of the industrial sector, harbour, the informal settlement of Hangberg and the beginning the mountainous terrain of The Sentinel. This dissertation proposes that the brine water be used for salt harvesting, via shallow pans, where naturally, the water will be evaporated from these pans, leaving salt crystals behind to be used in industry, as well as the implementation of sustainable energy devices to help supplement this extensive energy consuming process. With great infrastructure comes great responsibility, therefore the design of this infrastructure must be coupled with public activities. Building something that helps our future livelihood must be something that people can also interact with, and identify with, thereby creating a physical and emotive landmark.